Annexin A8 Is a Prognostic Marker and Potential Therapeutic Target for Pancreatic Cancer. Issue 1 (January 2015) - Pimiento, Jose M.; Chen, Dung-Tsa; Centeno, Barbara A.; Davis-Yadley, Ashley H.; Husain, Kazim; Fulp, William J.; Wang, Chen; Zhang, Anying; Malafa, Mokenge P.
<x xml:space="preserve">Abstract</x> Objectives We investigated whether annexin A8 (A-A8), a Ca2+-binding protein overexpressed in pancreatic cancer, plays a role in cell growth and migration and investigated its association with pancreatic cancer prognosis. Methods Clinicopathological features and associations between increased A-A8 expression (determined by immunohistochemistry) and histologic grade were studied in a tissue microarray of 90 patients with resected stage I/II pancreatic cancer. We investigated A-A8's effect on cell migration, proliferation, and colony formation in 2 pancreatic cancer cells (BXPC-3 and Panc-1). Statistical analyses included Fisher exact test, t test, analysis of variance, and survival analysis. Results Western blot showed increased A-A8 expression in human pancreatic cancer cells, with A-A8 knockdown in BXPC-3 and Panc-1 cells demonstrating decreased cell viability (P = 0.017 and P = 0.001), migration (2.5 vs 0.9 mm and 1.6 vs 1 mm at 96 hours; P = 0.048 and P = 0.004), and colony formation (approximately 75% and 40% from scramble; P ⩽ 0.01), respectively. In our tissue microarray, A-A8 expression increased 5.9-fold (r = 0.31; P = 0.019) from low- to high-grade tumors, correlating with tumor grade (r = 0.23; P = 0.027). In addition, high A-A8 expression was associated with a decreased 5-year survival (P = 0.042). Conclusions Our study is the first showing that increased A-A8 expression is associated with poor prognosis in early-stage pancreatic cancer, thus supporting its further investigation as a future therapeutic target and prognostic marker.